IN THE LABYRYNTH OF THE “DEFINITIVE BOOK”: NOTES ON THE BORGESIAN INFLUENCE IN HOROZOVIC’S TALHE - Irma Marić (Društvene i Humanističke Studije, 2020)
Irfan Horozovic is a prose writer who uses the elements of fantastic and outworldly in his fiction. In this paper, we are attempting to point to the elements of the fantastic-poetic model by referring to the poetics, ethics and aesthetics of Irfan Horozovic’s body of work. The starting point on such a vertical line undoubtedly belongs to his work Talha or the Shadrvan Garden, which is also known in the literary criticism as the ‘definitive book’, that is, the book by which Horozovic, as a Borgesian, made his big entrance into the world of literature.